2021
DOI: 10.3390/bioengineering8110152
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Evaluation of Biliary Atresia Patients to Predict Long-Term Outcome after the Kasai Procedure

Abstract: Kasai portoenterostomy (KP) represents the first-line treatment for biliary atresia (BA). The purpose was to compare the accuracy of quantitative parameters extracted from laboratory tests, US imaging, and MR imaging studies using machine learning (ML) algorithms to predict the long-term medical outcome in native liver survivor BA patients after KP. Twenty-four patients were evaluated according to clinical and laboratory data at initial evaluation (median follow-up = 9.7 years) after KP as having ideal (n = 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…For MRI quantitative analysis, liver and spleen volumes were measured by an abdominal radiologist with 15 years of experience in hepatobiliary imaging using a semiautomatic method with OsiriX ® version 3.3 software (Geneva, Switzerland) [ 17 , 18 ]. In detail, liver and spleen contours were manually traced at different levels on T2-weighted images with the closed polygon selection tool; then, the remaining boundaries were automatically outlined using the Grow Region (2D/3D Segmentation) tool.…”
Section: Methodsmentioning
confidence: 99%
“…For MRI quantitative analysis, liver and spleen volumes were measured by an abdominal radiologist with 15 years of experience in hepatobiliary imaging using a semiautomatic method with OsiriX ® version 3.3 software (Geneva, Switzerland) [ 17 , 18 ]. In detail, liver and spleen contours were manually traced at different levels on T2-weighted images with the closed polygon selection tool; then, the remaining boundaries were automatically outlined using the Grow Region (2D/3D Segmentation) tool.…”
Section: Methodsmentioning
confidence: 99%
“…A very promising technological advancement for the future of health care is predictive analytics [44][45][46][47], used to predict outcomes, events, and behaviors that will or may occur in the future. This technology has the potential to significantly transform health care systems in several countries, creating strong tools to identify and address heath threats, improve patient outcomes, and reduce the cost of medical care.…”
Section: Predictive Analytics and Personalized Geneticsmentioning
confidence: 99%
“…Schneider et al, for example, suggested that failure to normalize serum bilirubin within three months after Kasai should elicit prompt evaluation for LT as extended native liver survival is exceptional among these patients [50]. Moreover, though a "Kasai success predicting score" remains far from reality, other groups support more research in that direction as part of BA management-a strategy that would allow early primary transplantation [47,54,[57][58][59][60][61].…”
Section: Steadily Increasing Prioritization Requestsmentioning
confidence: 99%